Study on the Effect of Two Different Transfusion Methods in Neonates with Hyperbilirubinemia Induced by Non-Blood-Group Antibodies - Wu K; Chen L; Huang H (International Journal of General Medicine, 2021)
Kunhai Wu,1 Lufei Chen,1 Huifang Huang2 1Blood Transfusion Department, Fujian Provincial Maternity and Children’s Hospital, Fuzhou, Fujian, People’s Republic of China; 2Intensive Care Unit, Fujian Provincial Maternity and Children’s Hospital, Fuzhou, Fujian, People’s Republic of ChinaCorrespondence: Huifang HuangIntensive Care Unit, Fujian Provincial Maternity and Children’s Hospital, Fuzhou, Fujian, People’s Republic of ChinaTel +86 13906913057Fax +86 591-87555474Email 190596715@qq.comPurpose: The study aimed to analyse the clinical effect of homotype ET method and compatible ET method in neonates with hyperbilirubinemia caused by non-blood-group antibodies (non-blood-group antibodies refers to due to cause other than blood-group antibodies) as well as to provide relevant reference materials for clinical diagnosis and treatment in Fuzhou city.Patients and Methods: Between January 2011 and December 2020, a total of 125 neonates, who were admitted to the Sentinel hospital of Fuzhou city, Fujian Provincial Maternity and Children’s Hospital for hyperbilirubinemia and treated with ET therapy were selected. They were divided into homotype ET (n=32) and compatibility ET (n=93) treatment groups. We analysed changes in serum total bilirubin (STB), serum indirect bilirubin (SIB), and platelet count before and after ET; retrospectively analysed the neonates’ clinical data; and compared findings between the 2 groups.Results: The homotype ET group and the compatible ET group showed higher STB, SIB, and platelet levels before ET and decreased levels of the same after ET; the difference was statistically significant (P< 0.001). Compared with the compatible ET group, the decreases in STB, SIB, and platelet count in the homotype ET group showed no significant difference (P> 0.05).Conclusion: ET therapy is the most timely and effective treatment method for severe hyperbilirubinemia in neonates clinically, and the effects of homotype and compatible ET are similar.Keywords: hyperbilirubinemia, exchange transfusion, neonate, homotype, compatibility